ANALYSIS OF THE IMPLEMENTATION OF CURRICULUM 2013 TEACHING BOOK IN IPS SUBJECTS AT SMP MEDAN CITY - Nurmairina Nurmairina (Sensei International Journal of Education and Linguistic, 2021)
This study examines the implementation of the 2013 curriculum on social studies textbooks in five junior high schools in Medan. The problem that arises in this research is how to implement the 2013 curriculum textbook in social studies lessons. This study aims to uncover and analyze (1). Implementation of the 2013 curriculum in social studies textbooks, (2). suitability of language and graphics in social studies textbooks, (3). How are the obstacles and solutions faced by teachers in implementing the 2013 curriculum textbooks in social studies subjects. This type of research is qualitative research using descriptive statistical approaches and descriptive qualitative. The sample in this study was the 2013 curriculum book. The implementation of the 2013 curriculum in the social studies textbook was measured using a questionnaire. t_(count) is -0.869 while the value is 2.074 at the 0.05 significance level with dk = 22 t_(table) ?2.50. So it can be concluded that Ho is accepted, Ha is rejected, thus the results of the study show that, most of the 2013 curriculum books are not in accordance with the 2013 curriculum and are not yet suitable to be used as textbooks for class VII students, so they still need re-analysis results. From the results of interviews with linguists and graphists, it is known that most of the language and graphics presentations in social studies textbooks need to be revised again. From the results of interviews with teachers, it is known that there are several obstacles in using social studies textbooks such as the availability of books, limited material in books, so that the teacher anticipates by distributing 1 book to 2 students due to lack of books, and for material shortages the teacher still uses additional books other than books 2013 curriculum.